Evidence-Based Caries Prevention - Eden, Ece (Springer International Publishing : Imprint: Springer, 2016)
This book aims to define the etiological factors in dental caries and to guide the clinician towards methods of caries prevention that are evidence based. The coverage includes discussion of the active role of the biofilm and the oral environment and emphasizes the multifactorial etiology of dental caries. The opening chapters describe the early detection and diagnosis of dental caries, highlight the value of caries risk assessment to the patient, and explain the dynamic process of the demineralization-remineralization cycle. Information is presented on the action of fluoride, and the evidence relating to the use and effectiveness of remineralization agents and biomimetic materials is reviewed. Additionally, the effects of antimicrobials such as chlorhexidine and ozone are summarized. Further chapters focus on dietary counseling (with information on sweeteners and probiotics), the effectiveness of sealants in caries prevention, and resin infiltration. The philosophy of prophylaxis and ways to improve patient compliance and achieve proper mechanical plaque removal are discussed. The book is concluded with a chapter discussing preventive actions in representative cases.